Hypervelocity impact induced mechanoluminescence of phosphors - Baghel, R N; Parganiha, S; Chandra, B P (Recent Research in Science and Technology, 2012)
Phosphors are materials doped with one or more impurities that give cold light emission when excited. When a high velocity projectile strikes the backside of a metal plate whose front side is coated with phosphor, then the light emission takes place from the phosphor. ZnS:Mn is an important phosphor which has many applications. It is observed that, when a projectile moving with a hypervelocity makes an impact on to the metal plate coated with ZnS:Mn phosphors, then intense mechanoluminescence (ML )is produced.. The present paper reports the kinetics of ML induced by hypervelocity impact on ZnS:Mn phosphors ,whereby a good agreement is found between the experimental and theoretical results.